THE KNOWLEDGE AND PRACTICE ON MANAGEMENT OF DIABETES MELLITUS AMONG PATIENTS ATTENDING OUT PATIENT DEPARTMENT - S.POONGUZHALI (International Journal of Pharma and Bio Sciences, 2015)
The rising of diabetes in developing countries is closely associated with industrialization and socioeconomic development, Genetic predisposition, lifestyle changes due to rapid urbanization, high intake of fast food without any activity in the form of exercise in urban area may all be contributory to high prevalence of diabetes. The Objectives are to assess the knowledge and practice of patients with diabetes mellitus, to determine the association between knowledge and practice of diabetes mellitus with selected demographic variables and to distribute a teaching module. Descriptive study design was selected to assess the knowledge and practice on management of diabetes mellitus among patients attending outpatient department of Government General Hospital Chennai was carried among 200 patients attending outpatient department, identified from interview schedule. Percentage, mean, standard deviation, chi-square test, student‘t’ test and ‘F’ test were used based on objectives of the study. 43% of patients had inadequate knowledge about the disease, 49.5% had inadequate knowledge about the diet, 64.5% had inadequate knowledge about the exercise and 42.5% of patient had inadequate knowledge about the drug. There is a high association between the knowledge and practice, p value=0.01. By conducting health education programme the knowledge of diabetes patients will definitely improve, which will leads to practice towards the management of diabetes mellitus.